Hough's Cardiorespiratory Care / An Evidence-based, Problem-Solving Approach - Hough Alexandra (Elsevier, 2018)
This book stimulates critical thought and ensures that practice is evidence based. Preface, Acknowledgements, Physiology and Pathology, Physiological Basis of Clinical Practice, Assessment, Respiratory Disorders, Cardiovascular Disorders, General Management, Physiotherapy Techniques, Physiotherapy to Increase Lung Volume, Physiotherapy to Increase Lung Volume, Physiotherapy to Clear Secretions, Physiotherapy to Decrease the Work of Breathing, Pulmonary Rehabilitation, Physiotherapy for People with Cardiovascular Disorders, Cardiac Rehabilitation, Complications, Physiotherapy for Surgical Patients, Modifications for Different Types of Surgery, Physiotherapy for Specific Groups of People, Infants, Children, Hyperventilation Syndrome, Elderly People with Cardiorespiratory Disease, Palliative Respiratory Physiotherapy, Critical Care, Critical Care and Support and Monitoring, Physiotherapy for Critically Ill Patients, Modifications for Different Disorders, Does it Work?, Evaluation of Cardiorespiratory Physiotherapy, Glossary, Index.